The experiential ontology of Hannah Arendt - Maslin, Kimberly (Lexington Books, 2020)
Martin Heidegger's influence on the thought of Hannah Arendt has been frequently noted, but the precise nature of Arendt's critique of her mentor is less understood. Kim Maslin argues that Arendt's work attempted to transform fundamental ontology for responsible use in the public realm.